Ego state counseling to increase gender awareness in LGBT adolescents - Asyraf, Muhammad Qais; Isti'adah, Feida Noor Laila; Sugara, Gian Sugiana (Jurnal Konseling dan Pendidikan, 2024)
This study aims to test the effectiveness of the ego state counseling model in increasing gender awareness in gay adolescents, focusing on aspects of masculinity, femininity, and gender neutrality. This study used a single case study design with an ABA approach. The subject of the study was a 12th grade high school student in Tasikmalaya who was identified as part of the LGBT group and showed feminine behavior. The ego state counseling intervention was carried out for 5 sessions, with a duration of 45-60 minutes per session. The measuring instruments used were the Bem Sex Role Inventory (BSRI) to measure gender awareness and the Mental Health Continuum-Short Form (MHC-SF) to measure the dimensions of mental well-being. The results showed that the ego state counseling intervention was effective in increasing gender awareness in the subjects. There was a significant increase in the masculine score (d = 1.84) and a significant decrease in the feminine score (d = 3.55). The dimensions of mental well-being also showed a significant increase, especially in social well-being (d = 2.45). This study contributes to guidance and counseling services by demonstrating the potential of ego state counseling as an effective intervention to increase gender awareness and mental health in gay adolescents. These findings may assist counselors in developing more specific and targeted intervention strategies to help gay adolescent construct healthier gender identities and achieve better mental well-being.